Predictive factors for relapse in triple-negative breast cancer patients without pathological complete response after neoadjuvant chemotherapy - Toss, Angela; Venturelli, Marta; Civallero, Monica; Piombino, Claudia; Domati, Federica; Ficarra, Guido; Combi, Francesca; Cabitza, Eleonora; Caggia, Federica; Barbieri, Elena; Barbolini, Monica; Moscetti, Luca; et al. (Frontiers in Oncology, 2022)
Triple-negative breast cancer (TNBC) patients who do not obtain pathologic complete response (pCR) after neoadjuvant chemotherapy (NACT) present higher rate of relapse and worse overall survival. Risk factors for relapse in this subset of patients are poorly characterized. This study aimed to identify predictive factors for relapse in TNBC patients without pCR after NACT. Women with TNBC treated with NACT from January 2008 to May 2020 at the Modena Cancer Center were included in the analysis. We identified 142 patients with median follow-up of 55 months. After NACT, 62 patients obtained pCR (43.9%). Young age at diagnosis (< 50 years) and high ki-67 (>20%) were significantly associated to pCR. Lack of pCR after NACT resulted in worse 5-year event-free survival (EFS) and overall survival (OS). Factors independently predicting EFS in patients without pCR were the presence of multifocal disease (HR 3.77; 95% CI, 1.45–9.61; P 0.005) and Residual Cancer Burden (RCB) III (HR 3.04; 95% CI, 1.09–9.9; P 0.04). Neither germline BRCA status nor HER2-low expression were associated to relapse. These data can be used to stratify patients and potentially guide treatment decision-making, identifying appropriate candidates for treatment intensification especially in neo/adjuvant setting.